STUDI KELAYAKAN KONDISI MINYAK TRAFO EXISTING - Dwinanto, Dwinanto (Mesin, 2016)
Electricity became the main support in the Steel Industry. Transformer as one tool to change the power supply voltage. Transformer uses transformer oil as the fluid insulation. Transformer oil must have good insulating properties. To determine the feasibility condition of transformer oil, one of the ways used is a test quantity of oil. Â In this study used transformer oils; Korean products (sample 1), the new transformer oil domestic product (sample 2), as well as transformer oil mix with the existing transformer oil transformer oil in the country by volume mixing ratio in percent 40 and 60 (sample 3). Methods of tests performed, among others; testing Gas Chromatography Mass - Spectrometry (GCMS), testing Thermal Gravimetric Analysis (TGA), the test car Gas Chromatography (GC) and frosted tester. standard used to validate the test results refers to the testing standard ANSI / IEEE C57.104. Results of the test results obtained some part of them; GCMS resulted transformer oil has a compound that is either present in the sample 2 because it has no sulfur compounds, on TGA shows the sample who have weight loss that small is sample 1 and GC resulted sample 2 results were excellent because the oil in new condition, and also Diffuse test results shows good breakdown voltage tester contained in samples 2 and